2021
DOI: 10.3390/app11083624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PEMF on Muscle Oxygenation during Cycling: A Single-Blind Controlled Pilot Study

Abstract: Pulsed electromagnetic fields (PEMFs) are used as non-invasive tools to enhance microcirculation and tissue oxygenation, with a modulatory influence on the microvasculature. This study aimed to measure the acute effect of PEMF on muscle oxygenation and its influence on pulmonary oxygen kinetics during exercise. Eighteen male cyclists performed, on different days, a constant-load exercise in both active (ON) and inactive (OFF) PEMF stimulations while deoxyhemoglobin and pulmonary oxygen kinetics, total oxygenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Nine male sedentary young people participated at this study (Table 1). Based on the effect size evident in Trofè et al [15,26] G * power software, version 3.1.9.2 (Kiel, Germany), predicted that a total sample size of 8 would give sufficient power (0.80) to detect a significant difference at alpha level of 0.05. One additional participant was included to ensure the availability of data in case of missing or corrupted data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine male sedentary young people participated at this study (Table 1). Based on the effect size evident in Trofè et al [15,26] G * power software, version 3.1.9.2 (Kiel, Germany), predicted that a total sample size of 8 would give sufficient power (0.80) to detect a significant difference at alpha level of 0.05. One additional participant was included to ensure the availability of data in case of missing or corrupted data.…”
Section: Methodsmentioning
confidence: 99%
“…Trofè et al [15] investigated the effect of PEMF stimulation in semi-professional cyclists. The authors found that stimulation applied during a heavy constant-load exercise was able to enhanced the rate of muscle oxygen extraction and utilization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focused magnetic waves have been deployed to overstimulate neuronal mitochondria, which causes them to overheat and die off essentially. This is an experimental treatment for glioblastoma [90,91]. It seems that one could target areas including the motor neurons and stimulate them with a to-be-determined therapeutic level to support their survival, as Dr Tedone has done with nutraceuticals for individuals suffering from motor neuron diseases such as ALS [7].…”
Section: Pulsed Electromagnetic Field (Pemf) -Head and Trunkmentioning
confidence: 99%
“…Given the importance of oxygen uptake in sport activity [ 23 ], especially in aerobic disciplines (e.g., cycling), we sought to investigate the PEMF’s effect during exercise to assess its influence on muscular activity. We know from our previous study that PEMF stimulation results in a higher O 2 muscle supply during exercise through increased O 2 release and uptake [ 24 ]. We thus hypothesize that PEMF stimulation could improve the muscular response due to a higher amplitude of muscular activity generated by the enhancement of muscular contraction mechanisms.…”
Section: Introductionmentioning
confidence: 99%